The Spatial Transformation and Sustainability of Development in the New City Areas of Metro Tanjung Bunga, Makassar City - Batara Surya; Syafri Syafri; Haeruddin Saleh; Emil Salim Rasyidi (Faculty of Geography, Universitas Gadjah Mada, 2021)
The spatial transformation of the new city area of Metro Tanjung Bunga Makassar City has an impact on the conversion of productive agricultural land to urban industry. Changes in land use coupled with an increase in socio-economic activities lead to changes in spatial structure, spatial patterns, and a decrease in environmental quality in the direction of changes in the community's socio-economic system. This study aims to analyze: (1) Spatial transformation works as a determinant of the sustainability of the development of new urban areas, (2) The effect of changes in land use, activity systems, population mobility, and transportation systems on environmental degradation. This study uses a combination of qualitative-quantitative approaches sequentially. Data was obtained through observation, in-depth interviews, surveys, and documentation. The number of respondents in this study was determined as many as 250 which was carried out purposively. The results showed that the development of the new city area of Metro Tanjung Bunga which was predominantly developed for commercial activities, services, tourism, and large-scale settlements supported by transportation infrastructure development had an impact on urban sprawl, morphological changes, spatial segregation, and hierarchical differences in meeting the needs of the population. The results of the study indicate that changes in the use of space in the new urban area have led to changes in the single social formation of the local community towards multiple social formations. Furthermore, changes in land use, activity systems, and transportation systems have a positive correlation to environmental quality degradation with a determination coefficient of 60.8%. This study recommends the development of the new city area of Metro Tanjung Bunga towards the creation of social, economic, and environmental sustainability through the support of policies of the Makassar City Government in the future.